2021
DOI: 10.1142/s1363919621500663
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Champions’ Activities and Influences in Organisations — A Literature Review

Abstract: Innovation champions often play a pivotal role in facilitating new ideas and technology-based innovations within organisations. The rise of digital technology has led to radical changes in the nature of innovation and calls for an assessment of existing knowledge on innovation champions’ activities and their influence on organisations and networks. This paper provides a systematic, interdisciplinary literature review on innovation champions from an individual and organisational perspective. Based on a search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Champions actively pursue new product ideas, evolve them into innovations, and bring them to market (Schon, 1963). Champions are associated with pursuing opportunity to create value for the organization (e.g., Howell and Higgins, 1990), and take charge of the full innovation process (Hölzle et al, 2010;Drechsler et al, 2021). In contrast, disseminators in our case study created value for a particular user group, only addressed the gap between initial prototyping and broad diffusion, and delegated commercialization to others.…”
Section: Dissemination Of User Innovationsmentioning
confidence: 94%
“…Champions actively pursue new product ideas, evolve them into innovations, and bring them to market (Schon, 1963). Champions are associated with pursuing opportunity to create value for the organization (e.g., Howell and Higgins, 1990), and take charge of the full innovation process (Hölzle et al, 2010;Drechsler et al, 2021). In contrast, disseminators in our case study created value for a particular user group, only addressed the gap between initial prototyping and broad diffusion, and delegated commercialization to others.…”
Section: Dissemination Of User Innovationsmentioning
confidence: 94%
“…Scholars have started to investigate how strategic actors use politics to get support for their initiatives, exploring areas of framing and issue-selling that promote innovation (Lu et al, 2019;Röth et al, 2019). This literature conceives political behavior as how actors achieve their goals in power struggles with others with heterogeneous and conflicting interests (Drechsler et al, 2021;Markham, 1998), and it typically focuses on the actions and motivations of innovation promotors, or champions (e.g., Kelley & Lee, 2010). This research offers insight into the functional consequences of political behavior for product innovation, for example by speeding up the internal process (e.g., Dayan et al, 2012) and making it more flexible (e.g., Röth et al, 2023).…”
Section: Recent Advancementsmentioning
confidence: 99%
“…For instance, in their influential meta-analysis on individual-level innovation predictors, Hammond et al (2011) Existing literature reviews on the topic tend to examine a specific part of the implementation stage, such as idea championing (Drechsler et al, 2021); focus on specific types of implementers, such as innovation leaders (Kremer et al, 2019); or adopt broader multilevel approaches that include individual, group, organizational and other levels (Anderson et al, 2014;Kim & Chung, 2017;Zennouche et al, 2014). Although these reviews have offered important insights into their particular focus areas, their views of the individual remain restricted to a few notable individual factors, such as influencing skills (Drechsler et al, 2021) or knowledge-sharing behaviour (Kremer et al, 2019). Apart from these reviews, extant research has identified several individual-level factors contributing to idea implementation, including social skills (Baer, 2012), knowledge and experience (Birdi et al, 2016), cognitive abilities (Cerinšek & Dolinsek, 2009), motivation (Zennouche et al, 2014) and personality traits (Griffin et al, 2009).…”
Section: Views On Idea Implementationmentioning
confidence: 99%
“…Existing literature reviews on the topic tend to examine a specific part of the implementation stage, such as idea championing (Drechsler et al, 2021); focus on specific types of implementers, such as innovation leaders (Kremer et al, 2019); or adopt broader multilevel approaches that include individual, group, organizational and other levels (Anderson et al, 2014; Kim & Chung, 2017; Zennouche et al, 2014). Although these reviews have offered important insights into their particular focus areas, their views of the individual remain restricted to a few notable individual factors, such as influencing skills (Drechsler et al, 2021) or knowledge‐sharing behaviour (Kremer et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%